The Influence of Food Security Program Through Arts and Culture Towards Sustainable Development in Mahulu District, East Kalimantan Province - Rahcmad Budi Suharto; Geh, Bonifasius Belawan; Hasid, Zamruddin; Amalia, Siti (PT Inovasi Pratama Internasional, 2023)
This research examines the implementation of the